Fatigue Behaviour of Reinforced Concrete Beam Strengthened With a CFRP Reinforced System - J. L. Esteves (2004)
The flexural strengthening and rehabilitation of reinforced concrete elements, with CFRP reinforced system based in unidirectional composites, exhibit superior fatigue performance to that of steel. Previous research has [1] shown that the dominant factor in the fatigue of FRP-strengthened beams is the fatigue of the steel rebars structure. For the correct understanding of the fatigue behaviour of CFRP-strengthened beams considering ageing effects, a reduce scale beam experimental testing programme was implemented in the scope of a research and development project POCTI/36059/ECM/2000 Behaviour and Design of Concrete Structures Strengthened with FRP Considering Ageing Effects, supported by Fundação para a Ciência e Tecnologia, Portugal. The CFRP reinforced system (unidirectional composite strips) has been calculated to be able to double the static ultimate load of the reinforced concrete beam. The flexural fatigue behaviour of the beams was analysed, utilising an Instron servo-hydraulic four points bending apparatus testing, and different load parameters.